Communication—Cathodic Platinum Dissolution Studied Using a Channel Flow Double Electrode. Issue 5 (11th February 2016) - Wang, Zhongqi; Tada, Eiji; Nishikata, Atsushi
Abstract : Cathodic platinum dissolution (CPD) was analyzed in 0.5 and 5 M H2 SO4 solutions at 25 and 65°C using a channel flow double electrode (CFDE). A polycrystalline Pt plate and a commercial carbon-supported Pt nanoparticles (Pt/C) were employed as the Pt working electrodes. An increase in temperature from 25 to 65°C resulted in substantial enhancement of CPD by 5 times. An increase in the concentration of the H2 SO4 solution also moderately enhanced the CPD. For the same Pt surface area, CPD from Pt/C was observed to be ca. 40% of that from the bulk plate.